Everyday Discrimination, Depressive Symptoms, and Suicide Ideation Among African American Men. Issue 1 (2nd January 2021) - Goodwill, Janelle R.; Taylor, Robert Joseph; Watkins, Daphne C.
Abstract : Suicide has remained a leading cause of death among African American males, yet empirical investigations that focus on the experiences of this group are limited. Therefore, we aim to interrogate the impact of everyday discrimination as a risk factor for depressive symptoms and suicide ideation among African American men. Data were drawn from the African American male subsample of the National Survey of American Life ( n  = 1, 271). Path analysis and tests for indirect effects were used to examine relationships between everyday discrimination, depressive symptoms, and suicide ideation. Three sources of everyday discrimination were examined (any everyday discrimination, race-based everyday discrimination, and other everyday discrimination). Study findings revealed that race-based everyday discrimination was the only type of discrimination that was significantly associated with both increased rates of depressive symptoms and suicide ideation. Further, the indirect effect from race-based everyday discrimination to suicide ideation via depressive symptoms was also statistically significant. Thus, the impact of daily encounters with discrimination extends beyond depressive symptoms and is related to higher rates of suicide ideation. Moreover, experiences with discrimination do not have to be overt to be harmful toward African American men's mental health. Culturally relevant suicide prevention interventions are needed to account for the role of discrimination in the lives of African American men.